Design of a Rover to precision agriculture applications - Archila Diaz, John Faber (2016)
The population growth associated with natural resources shortage, food demand increasing and the lack of manpower for agricultural activities generate important challenges to agriculture and engineering. The challenges imply the improvement of productivity with fewer resources, This scenario is consisted parameters that generally are in opposite directions. This work presents the development of a rover to agriculture (R2A) to support agriculturescouting tasks, the tasks will be in the future important tools to improve the productivity and enable the use of less agricultural supplies. The research presents the development of a rover for agriculture (R2A) to support scouting tasks; tasks that in the future will improve productivity and allowed the use of less agricultural supplies. The study begins with a bibliographic review of Robots for agriculture, Rovers, and agricultural Rovers developed by different research institutions. After the review is presented the work methodology based on mechanic and mechatronic design methodologies; in the development of the methodology are presented the general crop characteristics, the proposed of scouting tasks, the benchmarking developing mathematical models, CAD (Computer Aided Design ) models, simulations and tests in order to know the different features of the Rovers and agricultural robots. Using the knowledge gained in the course of work is proposed the concept of a rover for agriculture R2A, the concept is compared in simulations, and developed the detailed design using CAE tools (Computer Aided Engineering) after it built a prototype and tested. As results are presented comparative simulations of R2A, their mathematical modeling, R2A simulations in ideally conditions highlighting their skills, and finally R2A tests and comparison are presented.